Teaching of Ordinary Differential Equations Using the Assumptions of the PBL Method - Paulo Henrique Xavier; Renelson Ribeiro Sampaio; Leandro Brito Santos; Jose Vicente Cardoso (Universitas Diponegoro, 2020)
Mathematics is of fundamental importance to any natural sciences program (because it provides analytical and approximate results that can be simulated and modeled) and perhaps to other areas of human knowledge. Ordinary differential equations (ODEs) are especially of fundamental importance to engineering programs because the modeling of all phenomena of interest for these programs involves ODE solutions; at the same time, students experience difficulties when learning ODEs and about their applications to real physical scenarios. In this study, the problem-based learning method was used to study a group of mechanical engineering students at theSENAICIMATECUniversityCenter. The study analyzes the effectiveness of ODE instruction given through this program using the specified methodology. To consolidate the study, Conceptual Field Theory is used together with an evaluation of the results to observe student behaviors and attitudes in relation to actions arising from the method. At the end of the study, a questionnaire was completed by the students, with which they evaluated the effectiveness of the teaching methodology employed.